1994
DOI: 10.1007/bf02247482
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of behavioral sensitization in the rat: effects of direct and indirect dopamine agonists

Abstract: In the present study, the abilities of NPA (a direct DA receptor agonist) and amphetamine (an indirect DA receptor agonist) to induce short- and long-term behavioral sensitization were assessed in 11- and 17-day-old rats (age at initial injection). Rats were injected on 4 consecutive days with amphetamine (1.0, 2.5, or 5.0 mg/kg), NPA (1.0 mg/kg), or saline. A final test day occurred either 2 days (experiment 1) or 8 days (experiment 2) later. On the test day, rats given successive agonist injections received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 30 publications
9
41
2
Order By: Relevance
“…In order to facilitate successful visualized patch-clamp recordings, we typically use young rats (p15-19) and, therefore, we wanted to be certain that these animals would also show sensitization. As previously reported (McDougall et al, 1994), we found that young rats administered amphetamine for 5 consecutive days showed a progressive enhancement in their ambulation counts when compared with rats that received saline. We also observed enhanced stereotypy to amphetamine challenge in amphetamine-treated rats at 2 and 4 days after withdrawal that was no longer apparent at 8 days after withdrawal.…”
Section: Discussion Young Rats Exhibit Short-term Sensitization To Resupporting
confidence: 87%
See 1 more Smart Citation
“…In order to facilitate successful visualized patch-clamp recordings, we typically use young rats (p15-19) and, therefore, we wanted to be certain that these animals would also show sensitization. As previously reported (McDougall et al, 1994), we found that young rats administered amphetamine for 5 consecutive days showed a progressive enhancement in their ambulation counts when compared with rats that received saline. We also observed enhanced stereotypy to amphetamine challenge in amphetamine-treated rats at 2 and 4 days after withdrawal that was no longer apparent at 8 days after withdrawal.…”
Section: Discussion Young Rats Exhibit Short-term Sensitization To Resupporting
confidence: 87%
“…Most studies on behavioral sensitization to psychostimulants are performed on adult rats, although there are reports that demonstrate young rats also show sensitized behavioral responses to amphetamine (McDougall et al, 1994;Duke et al, 1997). Prior to initiating physiological investigations of glutamatergic synapses, we wanted to confirm that the young rats used in our physiological experiments exhibit a sensitized response to amphetamine.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitization seems to occur only when the sensitizing regimen is restricted to late pre-weanling life or later and when repeated drug exposure is paired with the testing chamber or when long pretreatment regimens are used. Sensitization may be limited to short treatment-to-test intervals (McDougall et al 1994;Tirelli and Ferrara 1997;Wood et al 1998) We found that in 4 to 5-week-old rats, which are ageequivalent to the beginning of peri-adolescence, pairing of stimulant exposure with the testing environment was not necessary to obtain sensitization. Rats received repeated treatment of cocaine in their home cages and exhibited locomotor sensitization to a challenge dose of cocaine (7.5 mg/kg) that was half the repeated treatment dose following a 1-h habituation in the context of a novel testing facility.…”
Section: Ontogeny Of Behavioral Sensitizationmentioning
confidence: 82%
“…Sensitization seems to occur only when the sensitizing regimen is restricted to late pre-weanling life or later and when repeated drug exposure is paired with the testing chamber or when long pretreatment regimens are used. Sensitization may be limited to short treatment-to-test intervals (McDougall et al 1994;Tirelli and Ferrara 1997;Wood et al 1998) although other studies indicate persistent sensitization Zavala et al 2000).…”
Section: Ontogeny Of Behavioral Sensitizationmentioning
confidence: 99%
“…Duke, O'Neal, and McDougall (1997) observed significant behavioral sensitization in rats given 2.5 mg/kg AMPH, twice daily, during PDs 17–20. Other studies applied only one daily dose of AMPH (1.0, 2.5 or 5.0 mg/kg) or MPH (5.0, 10.0 or 15.0 or 20.0 mg/kg) during PDs 17–20 (McDougall, Duke, Bolanos, & Crawford, 1994) or PDs 16–21 (McDougall, Collins, Karper, Watson, & Crawford, 1999) and reported behavioral sensitization when tested 24 or 48 hr after the induction phase.…”
Section: Discussionmentioning
confidence: 99%